Development administration: An overview - Dwivedi, O.P. (1997)
Tracing its lineage from Keynesianism and Post-War developments of 30s, the author discusses evolution of the concept of development administration in its three phases - from 1950s to 70s, 1980s and 1990s - highlighting characteristic features of each phase as also the decade of 1971-81 when its justification was severely questioned. He discusses four very significant features of the present decade, i.e., de-administered development, market-friendly development administration, value-neutral administration, and renewal of government service as a calling and then proceeds to give his views about challenges to development administration in the next century emanating from rising influence of religion and traditional values, political factors in public service management, and the necessity to rebuild moral government. - Reproduced
Keywords: Development administration